Kualitas Pelayanan Permohonan Surat Izin Praktik Dokter Pada Pelayanan Terpadu Satu Pintu (PTSP) Di Kelurahan Bintaro Kecamatan Pesanggrahan Jakarta Selatan - Sheila Puspita Kusumawati; Rahmat Salam (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Health is one thing that is very important and is a must that needs to be fulfilled in human life. The One Stop Integrated Service is an activity of Licensing and Non-Licensing based on delegation or delegation of authority from an institution or agency that has licensing and non-licensing authority whose management process starts from the application stage to the document issuance stage which is carried out in one place. The purpose of this study is to describe the quality of public services in order to determine the quality of Health Worker Practice Permit Services in the One-Stop Integrated Service (PTSP) in Bintaro Village. The method used is descriptive with a quantitative approach. The population in this study are applicants for Administrative services Applications for Health Worker Practice Licenses in One-Stop Integrated Services (PTSP) in Bintaro Village in 2022 as many as 344 applicants using non-probability sampling. The sample technique used is purposive sampling. Researchers use indicators of service quality, namely tangibles,reliability, responsiveness, assurance, empathy. The research results obtained on the overall service quality indicator were good, namely 74.65%. The empathy indicator obtained the highest percentage results compared to other indicators, namely 79.39%. The one-day service indicator, which focuses on the reliability indicator, yields lower results than other indicators, namely only 69.65%. This shows that 81.8% has an effect on service quality, while the remaining 18.2% is influenced by other factors not examined in this study. Recommendations, it is hoped that PTSP will increase the number of employees, computers and other supporting tools so that services are more effective and efficient.